Case study: using monitoring of body composition data obtained by bioimpedance, in training of an elite male runner - Rebeyrol, J.; Moreno, M. V.; Ribbe, E.; Vannicatte, A. (Procedia Engineering, 2010)
This study wants to investigate if multi-frequency bioimpedance analysis; which is non-invasive, quick and mobile; and its indicators can be used like a tool for helping technical staff to improve performance, by optimizing training load, specific hydration and specific nutrition of an elite male runner. The principal results of this study are that BIA monitoring allowed to explain body weight variations, to optimize hydration state and to check fatigue state during the season. To conclude, BIA might be use in sport routine in order to monitor training load, hydration and nutrition during all the season.